Vpliv dinamične posturalne kontrole na test skladnosti gibanja telesa - Kocjan, Andrej (Šport (Ljubljana), 2020)
There are few studies about the effect of dynamic postural stability on functional movement performance. The aim of the present study was to investigate the effect of dynamic postural control and trunk muscles endurance on the score of functional movement screen test. Nineteen young participants were enrolled in the study. Their mean (standard deviation) age was 19.7 +- 5.1 years, weight was 71.6 +- 10.5 kilograms and height were 177 +- 7.6 centimetres. All subjects performed functional movement screen test (without shoulder mobility test), Y - balance test, prone plank, side plank and Biering-Sorensen test. Pearson correlation coefficient was used to measure the correlation between the tests. The level of statistical significance was set to p < 0.05. The results showed statistically significant moderate correlation (r = 0.534 - 0.456; p < 0.049) between Y - balance test and the score of functional movement screen test. The sensory-motor control of trunk muscles and the strength of hip abductor and extensor muscles seem to be important factors that affect the performance of basic movement patterns typically seen in sport and daily life.
Keywords: basic movement patterns; enostavni gibalni vzorci; functional movement screen; gibanje telesa; postural control; posturalna kontrola; skladnost; stability; stabilnost